Development of Game-Based Interactive Modules to Increase Interest in Learning the Qur'an Hadith - Febriani, Windi; Thaha, Hisban; P, Andi Achru (Educational Journal of Learning Technology, 2025)
This study aims to develop and evaluate a game-based interactive digital module designed to enhance students’ interest in learning Al-Qur’an Hadith, specifically Surah At-Tin, for fourth-grade students at MI Al-Mu’minun, Wajo Regency. The research employed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model with 18 students and one teacher as participants. Data were collected through observation, interviews, and questionnaires, and analyzed using both qualitative and quantitative approaches. The validation results showed the module was feasible, with scores from media experts (75%), material experts (95%), and linguists (88.8%). Practicality tests indicated very positive outcomes, with teacher assessments reaching 96.15% and student responses 93%. Effectiveness testing revealed a significant improvement in learning outcomes, from 69% (adequate) before using the module to 98% (very effective) after its implementation. These findings demonstrate that the game-based interactive module is valid, practical, and highly effective for supporting Al-Qur’an Hadith learning.